Evaluating the impact of a reduction in the generosity of disability benefits: The 2008 Spanish reform - José I. Silva; Judit Vall-Castello (Institute for the Study of Labor (IZA), 2012)
We evaluate the effects of a reduction in the generosity of disability benefits in Spain that occurred in 2008. The main objective of the reform was to reduce the amount of benefits for individuals that do not have a long contributory history as the reform introduced a disincentive to apply to the system if the individual does not have 35 years of effective contributions. Theoretical insights are gained with a life-cycle model with heterogeneous disabled workers. The model's simulations predict a reduction in the incentives to apply for disability benefits for partially disabled individuals who do not reach the 35 years of contributions. Diff-in-diff estimates are consistent with our model predictions.
urn:nbn:de:101:1-2012080812229
Keywords: C33; I18; H51; 330; disability benefits reform; life-cycle model; policy evaluation; Erwerbsunfähigkeitsrente; Reform; Erwerbsunfähigkeit; Ökonomischer Anreiz; Spanien